Ayia Sotira : a Mycenaean chamber tomb cemetery in the Nemea Valley, Greece - Smith, R. Angus K. (Prehistory Monographs, 2017)
Tomb 1 / Evangelia Pappi and Sevasti Triantaphyllou -- Tombs 2-6 / Mary K. Dabney, Panagiotis Karkanas, R. Angus K. Smith, Sevasti Triantaphyllou, and James C. Wright -- Geoarchaeological study / Panagiotis Karkanas -- Human remains / Sevasti Triantaphyllou -- Archaeobotanical remains / Georgia Kotzamani and Alexandra Livarda -- Wood charcoal macro-remains / Maria Ntinou -- Phytolith analysis / Georgia Tsartsidou -- Organic residue analysis / Maria Roumpou -- Conclusions -- Appendix: Medieval pottery and coins / Camilla MacKay and Alan M. Stahl.